2020
DOI: 10.1093/jxb/eraa237
|View full text |Cite
|
Sign up to set email alerts
|

Transposon insertions within alleles of BnaFLC.A10 and BnaFLC.A2 are associated with seasonal crop type in rapeseed

Abstract: In Brassicaceae, the requirement for vernalization is conferred by high expression of FLOWERING LOCUS C (FLC). The expression of FLC is known to be repressed by prolonged exposure to cold. Rapeseed (Brassica napus L.) cultivars can be classified into spring, winter, and semi-winter crop types, depending on their respective vernalization requirements. In addition to two known distinct transposon insertion events, here we identified a 4.422 kb hAT and a 5.625 kb long interspersed nuclear element transposon inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 60 publications
2
30
0
Order By: Relevance
“…The transcript levels of these Bna.FLC paralogs decreased significantly in the first 4 weeks of vernalization and remained below detection levels until the end of the vernalization period (Figure 3a). Interestingly, Bna.FLC.A10 and Bna.FLC.A02 were proposed to be the main genes that contribute to the vernalization requirement in winter rapeseed (Long et al, 2007; Raman et al, 2016; Schiessl, Quezada‐Martinez, Tebartz, Snowdon, & Qian, 2019; Wu et al, 2019; Yin et al, 2020). By looking at all Bna.FLC expression profiles, we found that Bna.FLC.C02 , Bna.FLC.C03 and Bna.FLC.C09a were not expressed in any of the stages of vernalization we analysed.…”
Section: Resultsmentioning
confidence: 99%
“…The transcript levels of these Bna.FLC paralogs decreased significantly in the first 4 weeks of vernalization and remained below detection levels until the end of the vernalization period (Figure 3a). Interestingly, Bna.FLC.A10 and Bna.FLC.A02 were proposed to be the main genes that contribute to the vernalization requirement in winter rapeseed (Long et al, 2007; Raman et al, 2016; Schiessl, Quezada‐Martinez, Tebartz, Snowdon, & Qian, 2019; Wu et al, 2019; Yin et al, 2020). By looking at all Bna.FLC expression profiles, we found that Bna.FLC.C02 , Bna.FLC.C03 and Bna.FLC.C09a were not expressed in any of the stages of vernalization we analysed.…”
Section: Resultsmentioning
confidence: 99%
“…Our data confirms that MITEs are closely associated to rice genes, concentrating in gene proximal upstream and downstream regions. Many examples of MITE insertions in 5’ and 3’ of genes that alter gene expression in different plants have accumulated over the years, including insertions in promoters enhancing (Zheng et al ., 2019; Shimada et al ., 2018; Yin et al ., 2020; Xu et al ., 2020) or repressing (Mao et al ., 2015; Xu et al ., 2020) transcription, or repressing translation (Shen et al ., 2017). MITEs have been shown to frequently contain transcription factor binding sites in plants, including rice (Morata et al ., 2018), suggesting a potential impact on promoter evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent contradiction between a conservative cut-and-paste mechanism of transposition and MITEs high copy number was highlighted short after MITE discovery (Feschotte et al ., 2002; Casacuberta and Santiago, 2003), but the mechanism by which MITEs amplify is still obscure. MITEs are tightly associated with plant genes (Santiago et al ., 2002; Lu et al ., 2012; Benjak et al ., 2009), and examples of these elements potentially altering gene expression have accumulated over the years (Santiago et al ., 2002; Lu et al ., 2012; Naito et al ., 2009; Yang et al ., 2005; Xu et al ., 2020; Zheng et al ., 2019; Yin et al ., 2020). Moreover, it has recently been shown that MITEs frequently contain Transcription Factor Binding Sites (TFBS) in plants, which may allow their mobilization to alter transcriptional networks by rewiring new genes (Morata et al ., 2018), and that they can induce structural variability through aberrant transposition events (Chen et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The data indicate that Bna.FLC.A10 is not only responsible for the high vernalization dependency of winter types, but also for the moderate vernalization dependency of semi-winter types. A recent study identified additional transposon insertions influencing expression in the promoters of Bna.FLC.A10 and Bna.FLC.A02 and concluded that Bna.FLC.A10 determines growth type in combination with Bna.FLC.A02 (Yin et al, 2020). Interestingly, swedes (ssp.…”
Section: Vernalization: Flc Fri and Vin3mentioning
confidence: 99%